Reduction of contrast agent volume utilization for cardiac catheterization in current clinical practice. (1st November 2022) - Stocker, Thomas J.; Massberg, Steffen; Hausleiter, Jörg
Abstract: Background: Cardiac catheterization procedures require intra-arterial contrast agent administration. The amount of utilized contrast agent volume (CAV) is a risk factor for contrast-induced side-effects. In this study, we assess trends and associations of CAV utilization in diagnostic cardiac catheterization (DCC) and percutaneous coronary intervention (PCI). Methods: All cardiac catheterization procedures reported for quality assurance between 2008 and 2018 in Germany were included. Available site, patient, and procedural parameters were analyzed. CAV was reported by interventional cardiologists after the procedure. Multivariate linear regression analysis was used to identify associated factors with clinically relevant CAV change (defined >10 ml). Results: We included 9, 106, 511 procedures (DCC: 5, 401, 525, PCI: 3, 704, 986). Median CAV of all DCCs was 80 (interquartile range, IQR 60–110) ml. CAV for DCC significantly lowered by 22% during the retrospective observational period ( p < 0.001) and significantly varied according to the leading diagnosis ( p < 0.001). We observed significant 2.5-fold variability of CAV between the catheterization laboratories (5th percentile: 40 ml, 95th percentile: 100 ml, p < 0.001). Median CAV for PCIs was 170 (IQR 120–223) ml. Independent associated factors for clinically relevant higher CAV use in PCI were male gender, coronary-artery-bypass-graft surgery, total coronary occlusion, ostial lesions, and multi-vessel coronary artery disease (all p < 0.001). Conclusions: The results of this large, multi-center study show significant lowering of CAV in clinical routine DCC, however, the large inter-site variability demonstrates the need for additional CAV reduction to further lower the risk of adverse side-effects. In PCI practice, CAV should be limited in the presence of the identified high contrast-dose scenarios. Highlights: Contrast agent volume utilization for diagnostic cardiac catheterization in clinical practice decreased by 22% during the last decade Significant 2.5-fold variability of median contrast agent volume between clinical institutions demonstrates the need for further contrast agent reduction in diagnostic cardiac catheterization Contrast agent volume used for percutaneous coronary intervention in clinical practice remained stable during the last decade Significant factors for contrast agent increase in percutaneous coronary intervention are prior CABG surgery, PCI of total coronary occlusion, ostial lesions, and multi-vessel CAD disease